2020
DOI: 10.22158/jecs.v4n4p39
|View full text |Cite
|
Sign up to set email alerts
|

Racial Variation in the Association between Suicidal History and Positive and Negative Urgency among American Children

Abstract: Background: Positive and negative urgency reflect specific facets of impulsivity and correlate with several health-related risk behaviors such as aggression, substance use, and suicide. Less is known about how positive and negative urgency are associated with suicidal behaviors of diverse racial groups.Aim: To investigate racial differences in the positive associations between positive and negative urgency and suicide in children in US. Materials and methods: This longitudinal study used the Adolescent Brain C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…In our study, it was found that depressed adolescents who exhibited suicidal behavior tended to behave more impulsively and experienced more irritable moods. This finding is consistent with the studies suggesting that, impulsivity associated with positive and negative affect is strongly associated with suicide risk in American children (Assari, 2020), that chronic irritability in childhood is a high-risk factor for suicide, especially when combined with depressive/anxious mood (Orri et al, 2018), and that adolescents with high levels of irritability are more likely to respond disproportionately to emotional stressors and engage in impulsive suicidal behavior (Benarous et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, it was found that depressed adolescents who exhibited suicidal behavior tended to behave more impulsively and experienced more irritable moods. This finding is consistent with the studies suggesting that, impulsivity associated with positive and negative affect is strongly associated with suicide risk in American children (Assari, 2020), that chronic irritability in childhood is a high-risk factor for suicide, especially when combined with depressive/anxious mood (Orri et al, 2018), and that adolescents with high levels of irritability are more likely to respond disproportionately to emotional stressors and engage in impulsive suicidal behavior (Benarous et al, 2019).…”
Section: Discussionsupporting
confidence: 91%